1991
DOI: 10.1177/088610999100600103
|View full text |Cite
|
Sign up to set email alerts
|

A Shelter: An Organization Like Any Other?

Abstract: Shelters for battered women have been idealized as collectivist organizations that empower residents and staff alike. Qualitative research at a battered women's shelter indicates that despite an implicit philosophy of empowerment , a shelter is indeed an organization like any other. Two separable organizational structures were identified: an egalitarian , collectivist structure for the relationships among staff members and a hierarchical structure for the relationships between staff members and residents . To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 12 publications
(19 reference statements)
1
25
0
Order By: Relevance
“…As can be seen from these researches (Dobash and Dobash, 1996 ;Epstein, et al, 1988 ;Fraser, 1989 ;McMillan, 2007 ;Rodriguez, 1988 ;Srinivasan and Davis, 1991) that focus on social and political aspects of shelters (I leave aside those work that are concerned with the psychological traits or situations of "abused" women), an important part of the studies on women's shelters throughout the North American and European world focus on the process of professionalization and/or the question of autonomy for the shelters that feminists are in charge of. The merits of these researches lie, on the one hand, in the fact that they assess the current state of the shelters with regards to the feminist values that has come out as a result of feminist movements in these countries, hence acting as important vehicles to rethink the ways in which shelters are organized.…”
Section: Shelters and Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen from these researches (Dobash and Dobash, 1996 ;Epstein, et al, 1988 ;Fraser, 1989 ;McMillan, 2007 ;Rodriguez, 1988 ;Srinivasan and Davis, 1991) that focus on social and political aspects of shelters (I leave aside those work that are concerned with the psychological traits or situations of "abused" women), an important part of the studies on women's shelters throughout the North American and European world focus on the process of professionalization and/or the question of autonomy for the shelters that feminists are in charge of. The merits of these researches lie, on the one hand, in the fact that they assess the current state of the shelters with regards to the feminist values that has come out as a result of feminist movements in these countries, hence acting as important vehicles to rethink the ways in which shelters are organized.…”
Section: Shelters and Statesmentioning
confidence: 99%
“…Funding meant certain obligations, like being able to cope with accounting procedures or hiring "professionals" as workers, so that feminists more often than not had to decide on whether or not to agree on these regulations. Despite all these discussions, even about 20 years after the first shelter was founded (Chiswick Women's Aid, founded in 1972 in the UK), several researchers were already talking about trends like "professionalization" or "psychologism" (understood as the substitution of therapy for politics) involved in dealing with the issue, especially for the US case (among others, we can talk about Dobash and Dobash, 1996 ;Epstein, et al, 1988 ;Fraser, 1989 ;Rodriguez, 1988 ;Srinivasan and Davis, 1991). On the other hand, there are also other recent researches that show that autonomy for feminist organizations that carry out shelter work is not unimaginable (for the cases of UK and Sweden, see McMillan, 2007).…”
mentioning
confidence: 99%
“…According to this approach, feminist organizations are an example of alternative organizations that are driven by a commitment to ideology and an egalitarian structure (Case and Taylor, 1979;Milofsky and Elion, 1988;Rothschild and Whitt, 1986). Proponents of feminist organizations argue that these organizations are highly democratic in their daily operation (Srinivasan and Davis, 1991;Epstein, Russell, and Silvern, 1988;Ferguson, 1984). But there are those who believe in Michels's (1962) "iron law of oligarchy": that even feminist organizations are by nature oligarchic because, like all other grass-roots organizations, they must compete for resources in order to survive.…”
Section: Managing Women Volunteersmentioning
confidence: 99%
“…Additional research has documented the enactment of agency practices and policies in some battered women's organizations inconsistent with feminist principles (Donnelly, Cook, & Wilson, 1999;Srinivasan & Davis, 1991). Still other research has indicated that graduating social work students are most knowledgeable of psychologically oriented theories of domestic violence, with very few being familiar with or endorsing feminist perspectives of this violence (Black, Weisz, & Bennett, 2010).…”
mentioning
confidence: 99%